Evaluation of contaminants of emerging concern in surface waters (rivers and lake) from Peru: Occurrence and environmental risk assessment - Jessica I. Nieto-Juárez; Noelia R. Sarzosa-Cano; Efraím A. Serna-Galvis; Ricardo A. Torres-Palma; David Fabregat-Safont; Ana M. Botero-Coy; Félix Hernández (Environment International)
This study represents one of the first efforts to investigate the presence and environmental risk of contaminants of emerging concern (CECs) in surface water of the main watersheds of the Department of Lima (Rímac River, Chillón River, and Lurin River), Department of Arequipa (Chili-Quilca-Vítor River, Cámana-Majes River, and Tambo River), and Department of Puno (Lake Titicaca) from Peru. Water samples were collected during two sampling campaigns (June and September-October 2023) in Lima and Arequipa, and one sampling campaign (April-May 2023) in Puno. A strategy combining qualitative and quantitative analysis of CECs was applied, based on liquid chromatography coupled to ion mobility-high resolution mass spectrometry (LC-IMS-HRMS) and tandem mass spectrometry (LC-MS/MS), respectively. A total of 16 pharmaceutically active compounds (PhACs) and other compounds (sweeteners, stimulants, UV filters, and preservatives) and 16 metabolites were identified by LC-IMS-HRMS with a high level of confidence, in addition to the 39 target PhACs quantified by LC-MS/MS. The watersheds of Lima showed the highest pollution in terms of the number of pharmaceuticals and concentration levels compared to the watersheds of Arequipa and Lake Titicaca (Puno), with antibiotics persisting from the upper watersheds to the lower watersheds in the rivers and the lake. For the environmental risk assessment, five different scenarios were considered depending on the water uses/destinations, and the multicriteria scoring method allowed to identification of relevant/concerning PhACs. Azithromycin, clarithromycin, erythromycin, ciprofloxacin, flumequine, trimethoprim, diclofenac, acetaminophen, losartan, valsartan, atorvastatin and metabolite O-desmethyl venlafaxine posed a high level of risk/concern. This information will facilitate the design of a Watch List for CECs, with future monitoring programs and environment risk assessments to protect vulnerable areas most affected by anthropogenic pollution.